Adolescent age is an independent risk factor for abnormal spirometry among people living with HIV in Kenya. (19th June 2018) - Attia, Engi F.; Maleche-Obimbo, Elizabeth; West, T. Eoin; Ndukwe-Wambutsi, Lilian; Kiptinness, Catherine; Cagle, Anthony; McGrath, Christine J.; Mugambi, Celestine K.; El Antouny, Neveen G.; Eskander, Sherry; Chung, Michael H.; Crothers, Kristina
Abstract : Objectives: As life expectancy of people living with HIV (PLWH) improves in low-income and middle-income countries (LMICs), the spectrum of HIV-related pulmonary complications may reflect a greater burden of chronic lung diseases as in high-income countries. We determined whether the risk of abnormal spirometry was greater among adolescent compared with adult PLWH at the Coptic Hope Center for Infectious Diseases in Nairobi, Kenya, and evaluated the role of other cofactors for abnormal spirometry. Design: We prospectively enrolled adolescent and adult PLWH for this cross-sectional study. Methods: Data collection included standardized questionnaires, clinical assessment, and prebronchodilator and postbronchodilator spirometry. Adolescents additionally underwent noncontrast chest computed tomography. Multivariable logistic regression determined associations of adolescent age with abnormal spirometry, adjusting for cofactors. Results: Of 427 PLWH, 21 (40%) adolescents and 64 (17%) adults had abnormal spirometry. Among adolescents, 80% had abnormal chest CTs, and 79% had at least one respiratory symptom. Adolescent age (adjusted odds ratio 3.22; 95% confidence interval 1.48–6.98) was independently associated with abnormal spirometry, adjusting for recent CD4 +, HIV clinical stage, low BMI, indoor kerosene use, smoking pack-years, and prior pulmonary tuberculosis. Additional important cofactors for abnormal spirometry included prior pulmonary tuberculosis (3.15; 1.70–5.58), kerosene use (1.77; 1.04–3.04) and smoking pack-years (1.05; 1.00–1.10). Adolescent age, prior pulmonary tuberculosis, and smoking pack-years were significantly associated with airflow limitation. Conclusion: Adolescent age was independently associated with increased risk of abnormal spirometry, particularly airflow limitation. Studies to improve prevention, detection, and management of chronic lung disease across the lifespan among PLWH are needed in LMICs. Abstract : Supplemental Digital Content is available in the text